Indicators of the force interaction of the track and rolling stock when a freight car runs on long irregularities, taking into account the action of longitudinal forces - E. A. Sidorova; V. O. Pevzner; A. I. Chechel’nitskiy (Вестник Научно-исследовательского института железнодорожного транспорта)
Authors describe formation mechanism of long irregularities of the railway track and the importance of their elimination for the track facilities. Based on the results of freight train operation modeling on long irregularities in the traction mode, an analysis of the processes occurring during the motion of heavy trains along a track with such deviations was carried out, modeling was carried out on the basis of the “Universal Mechanism” software package. Based on the results of the calculation, interaction between the track and the rolling stock in the vertical plane was assessed in terms of the magnitude of the vertical force and coeffcients: dynamics, stability margin, Nadal, unloading (in percent) of axle springs of freight car springs. Article analizes the nature of the infuence of the irregularity slope on the decrease in the vertical force transmitted from the wheel to the rail and the change in the traction force on the dynamics of freight cars in the train and passing on long irregularities of the longitudinal profle through the indicators of the vertical force.